Decolonising urban space: Observations from history in urban planning in Ruwa town, Zimbabwe, 1986-2015 - Terence Tapiwa Muzorewa; Vongai Z Nyawo; Mark Nyandoro (AOSIS, 2023)
This article calls for a shift of attention from the colonial urban planning methods to a focus on the post-colonial planning methods being adopted in new towns such as Ruwa. The core of the studies on urban planning in Zimbabwe has been centred on colonial established urban centres tending to promote the reproduction of spatial disparities in urban areas. This article argues that the only way to decolonise urban space in Zimbabwe is through establishing new towns which are not linked to the colonial planning system. All of the major towns in the country except Ruwa were established during the colonial era based on a planning system which segregated the African population. The colonial planning methods produced uneven development between areas occupied by Europeans and Africans. Although urban policies were deracialised during the post-colonial era, the physical nature of the built environment remained the same. While it was possible to change colonial urban policy, it was impossible to change, fundamentally, the spatial physical structures such as buildings, roads, water reticulation and sewerage systems. The spatial form of today’s Zimbabwean urban areas is an embodiment of colonial planning as this change entailed enormous financial costs. Ruwa town, therefore, demonstrates how modern urban development in the southern African country has been achieved on the basis of a totally different experience from the colonial established towns. Using insights from the town, the article illustrates the importance of studying post-colonial planning methods as a way of promoting the decolonisation of urban space.